Harmonisation process of Afghan asylum-seekers: a case study of Sivas satellite city - Canpolat, Medine Derya (Cappadocia Journal of Area Studies, 2020)
The subject of this research article is Afghan asylum-seekers – as the world’s most numerous displaced people – who have applied to Turkey for international protection. Its specific focus is on Afghan asylum seekers residing in Sivas satellite city who have applied for international protection. The study evaluates their personal experiences with harmonisation and integration, with the main objective being to investigate and analyse the problems they have faced during their harmonisation process, and to develop solutions to these problems. This research was designed as a case study – as a qualitative research methodology – and takes a theoretically interpretive perspective. Within the scope of this study, in addition to observations, in-depth interviews were conducted with seven female and eight male Afghan asylum-seekers who were reached through a snowball technique. As ascertained from the interviewees, the following issues were apparent: their harmonisation processes; the problems they faced in these processes; their expectations from local people; and their plans for the future. The findings related to the harmonisation process indicated that the respondent Afghan asylum-seekers are eager to obtain Turkish citizenship and integrate into society, although it was understood that they faced crucial problems in this regard, being the language barrier, economic insufficiency, and feelings of loneliness and strangeness. To overcome these hurdles, it is though that improving the given language courses in terms of quality and quantity will diminish the language barrier; applying government policies related to employment will decrease the financial insufficiency of Afghan asylum-seekers; and applying non-governmental policies to raise awareness among Afghan asylum-seekers of the opportunities that are open to them, will alleviate their lack of consciousness, and will lead to the development of a greater understanding among local people about the Afghan asylum-seekers, thus eliminating their feelings of loneliness and strangeness.